Actualization of Obstacles in the Implementation of Baitul Mal Wat Tamwil (BMT) in Micro-Enterprise Capital Financing - Nur Indah; Muhammad Achyar Hamid; Rahmatullah Rahmatullah (Mikailalsys Journal of Mathematics and Statistics, 2026)
Institutions that collect and distribute financing play a strategic role as funding pillars for micro-entrepreneurs, particularly for communities requiring business development support through accessible requirements and financing schemes that avoid excessive interest burdens. In the context of an expanding Muslim market segment, cooperatives and BMT represent microfinance institutions whose values are closely related to the ethical foundations of the Islamic economic system, which are derived primarily from the Qur’an and Sunnah and supported by ijma, qiyas, and other secondary sources of Islamic jurisprudence. This study aimed to examine the duties and functions of cooperatives and BMT in order to clarify their institutional roles and ensure that each operates in accordance with its respective principles. This study employed library research by reviewing written sources, including scientific journals, reference books, literature, encyclopedias, academic articles, scholarly works, and other relevant sources related to cooperatives, BMT, Islamic economics, and community-based economic development. The findings indicate that cooperatives and BMT both serve as important instruments for strengthening community finance, supporting micro-entrepreneurs, and advancing MSME development, yet they differ in institutional orientation, operational principles, and ethical foundations. The study concludes that a clear understanding of the distinct functions of cooperatives and BMT is essential to prevent overlapping roles and to optimize their contribution to economic development. These findings contribute to the literature on Islamic microfinance and people-centered economic systems, while offering practical implications for policymakers, cooperative managers, BMT administrators, and community economic actors in strengthening inclusive and ethically grounded financing institutions in Indonesia.